Fate of heavy metals in vertical subsurface flow constructed wetlands treating secondary treated petroleum refinery wastewater in Kaduna, Nigeria. Issue 1 (2nd January 2018) - Mustapha, Hassana Ibrahim; van Bruggen, J. J. A.; Lens, P. N. L.
ABSTRACT: This study examined the performance of pilot-scale vertical subsurface flow constructed wetlands (VSF–CWs) planted with three indigenous plants, i.e. Typha latifolia, Cyperus alternifolius, and Cynodon dactylon, in removing heavy metals from secondary treated refinery wastewater under tropical conditions. The T. latifolia -planted VSF–CW had the best heavy metal removal performance, followed by the Cyperus alternifolius -planted VSF–CW and then the Cynodon dactylon -planted VSF–CW. The data indicated that Cu, Cr, Zn, Pb, Cd, and Fe were accumulated in the plants at all the three VSF–CWs. However, the accumulation of the heavy metals in the plants accounted for only a rather small fraction (0.09–16%) of the overall heavy metal removal by the wetlands. The plant roots accumulated the highest amount of heavy metals, followed by the leaves, and then the stem. Cr and Fe were mainly retained in the roots of T. latifolia, Cyperus alternifolius, and Cynodon dactylon (TF < 1), meaning that Cr and Fe were only partially transported to the leaves of these plants. This study showed that VSF–CWs planted with T. latifolia, Cyperus Alternifolius, and Cynodon dactylon can be used for the large-scale removal of heavy metals from secondary refinery wastewater.